ANALISIS KEBUTUHAN BANDWIDTH DENGAN MODEL SHARING SYSTEM PADA MIKROTIK ROUTERBOARD 450G DI JARINGAN OFFICE STTA - Mardiana Irawaty; Ferry Mulyawan; Yenni Astuti (Compiler, 2017)
The limitations between the amount of bandwidth and users can make the internet slow. Observing the flow of data on the internet network is one way to identify the  bandwidth requirements which used on the STTA office network. This thesis analyzes the data traffic with sharing system model. The observed data is in the category of elastic flow rate, i.e: TCP (Transmission Control Protocol). The traffic data is converted to a measured data graph and then  analyzed  by  traffic  load,  throughput,  and  flow  of  loss  parameters.  The  highest observation value of traffic load is 0.37, Throughput of 9.3 Mbps (93%), and the flow of loss of 23%. From the results of the research, it can be concluded that in general internet network at STTA office is in good category.